Variable use of amiodarone is associated with a greater risk of recurrence of atrial fibrillation in the critically ill. Issue 1 (December 2016) - Mitrić, Goran; Udy, Andrew; Bandeshe, Hiran; Clement, Pierre; Boots, Rob
Abstract Background Atrial fibrillation is a common rhythm disturbance in the general medical-surgical intensive care unit. Amiodarone is a popular drug in this setting but evidence to inform clinical practice remains scarce. We aimed to identify whether variation in the clinical use of amiodarone was associated with recurrent atrial fibrillation. Methods This was a retrospective audit of 177 critically ill patients who developed new-onset atrial fibrillation after admission to a tertiary level medical-surgical trauma intensive care unit. Patterns of amiodarone prescription (including dosage schedule and duration) were assessed in relation to recurrence of atrial fibrillation during the intensive care unit stay. Known recurrence risk factors, such as inotrope administration, cardiac disease indices, Charlson Comorbidity Index, magnesium concentrations, fluid balance, and potassium concentrations, were also included in adjusted analysis using forward stepwise logistic regression modelling. Results The cohort had a median (interquartile range) age of 69 years (60–75), Acute Physiology and Chronic Health Evalution II score of 22 (17–28) and Charlson Comorbidity Index of 2 (1–4). A bolus dose of amiodarone followed by infusion (P = 0.02), in addition to continuing amiodarone infusion through to discharge from the intensive care unit (P < 0.001), were associated with less recurrent dysrhythmia. Recurrence after successful treatment was associated with ceasing amiodarone while an inotrope infusion continued (P < 0.001), and was more common in patients with a prior history of congestive cardiac failure (P = 0.04), and a diagnosis of systemic inflammatory response syndrome (P = 0.02). Conclusions Amiodarone should be administered as a bolus dose followed immediately with an infusion when treating atrial fibrillation in the medical-surgical intensive care unit. Consideration should be given to continuing amiodarone infusions in patients on inotropes until they are ceased.